Measurement of the Double Differential Dijet Mass Cross Section in pp(bar) Collisions at sqrt(s) = 1.96 TeV - (:unkn) unknown (My University, 2009)
This thesis presents the analysis of the double differential dijet mass cross section, measured at the DØ detector in Batavia, IL, using pp(bar) collisions at a center of mass energy of √s = 1.96 TeV. The dijet mass was calculated using the two highest pT jets

in the event, with approximately 0.7 fb-1 of data collected between 2004 and 2005.

The analysis was presented in bins of dijet mass (MJJ ) and rapidity (y), and extends the measurement farther in MJJ and y than any previous measurement. Corrections

due to detector effects were calculated using a Monte Carlo simulation and applied to data. The errors on the measurement consist of statistical and systematic errors, of which the Jet Energy Scale was the largest. The final result was compared to next-to-leading order theory and good agreement was found. These results may be used in the determination of the proton parton distribution functions and to set limits on

new physics.
Keywords: Partons; Hadron colliders; Quarks; Hadrons; Particles (Nuclear physics)